Reconhecimento de fala usando m?quinas de vetor de suporte (SVMs) - Coelho, Sandro Tomassoni (2005)
Abstract: The aim in this work it will be the studay of one recent technique of machine learning, called support vector machines, applied to isolated word, speech recognition problem. A new methodology was proposed for the classification of several classes. Also, the system performance was evaluated after the data normalization and the use of the principal componet analysis technique for data reduction.